2012
DOI: 10.1073/pnas.1117218109
|View full text |Cite
|
Sign up to set email alerts
|

Signal transducer and activator of transcription-3/suppressor of cytokine signaling-3 (STAT3/SOCS3) axis in myeloid cells regulates neuroinflammation

Abstract: Suppressor of cytokine signaling (SOCS) proteins are feedback inhibitors of the JAK/STAT pathway. SOCS3 has a crucial role in inhibiting STAT3 activation, cytokine signaling, and inflammatory gene expression in macrophages/microglia. To determine the role of SOCS3 in myeloid cells in neuroinflammation, mice with conditional SOCS3 deletion in myeloid cells (LysMCre-SOCS3fl/fl ) were tested for experimental autoimmune encephalomyelitis (EAE). The myeloid-specific SOCS3-deficient mice are vulnerable to myelin oli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
225
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 221 publications
(234 citation statements)
references
References 48 publications
8
225
1
Order By: Relevance
“…We previously demonstrated that mice with a specific deletion of the suppressor of cytokine signaling 3 (SOCS3) gene in myeloid cells (LysMCre-SOCS3 fl/fl ) develop early onset of a severe and nonresolving disease with features of atypical EAE, which is characterized by involvement of the CRB, rather than the SC, and ataxia, significant weight loss, axial rotation, and tremors (3). Importantly, we found that there was a striking neutrophil infiltration in the brain.…”
mentioning
confidence: 82%
See 3 more Smart Citations
“…We previously demonstrated that mice with a specific deletion of the suppressor of cytokine signaling 3 (SOCS3) gene in myeloid cells (LysMCre-SOCS3 fl/fl ) develop early onset of a severe and nonresolving disease with features of atypical EAE, which is characterized by involvement of the CRB, rather than the SC, and ataxia, significant weight loss, axial rotation, and tremors (3). Importantly, we found that there was a striking neutrophil infiltration in the brain.…”
mentioning
confidence: 82%
“…Active EAE was induced as previously described (3,34). Eight-to 12-wkold SOCS3 fl/fl or LysMCre-SOCS3 fl/fl mice were immunized s.c. with 100 mg MOG emulsified in CFA (supplemented with 2 mg/ml Mycobacterium tuberculosis) and injected i.p.…”
Section: Eae Induction and Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, SOCS3 has been shown to bind and directly inhibit the catalytic domains of JAKs via an evolutionarily conserved motif. Taking advantage of this role, a preclinical study has revealed that expression of SOCS3 in myeloid cells provides protection through deactivation of neuroinflammatory responses [11]. In non-small cell lung cancer (NSCLC) tumor samples, expression of SOCS3 has been shown to be lost due to promoter hyper methylation, an epigenetic change that reduces gene transcription.…”
mentioning
confidence: 99%